Why Care for Others?: How Bill Wilson Made Responsibility to Care a Matter of Life and Death in Alcoholics Anonymous. Issue 1 (2nd January 2023) - Simplican, Stacy Clifford; Graham, Ross; Suiter, Sarah V.; Morrison, Daniel R.
ABSTRACT: Joan Tronto's new paradigm of caring democracy bases citizenship on the need to ensure that all people receive and provide care equitably. But how exactly are citizens motivated to take up these caring responsibilities? The writings of Alcoholics Anonymous (AA) co-founder William 'Bill' Wilson provide one answer: he pathologizes the alcoholic – dooming him to inevitable relapse and death – to compel AA members to accept shared vulnerability and mutual care as the bedrock of sobriety and AA society. Wilson returns repeatedly to the threat of death to convince AA members to carry out their newfound caring and democratic responsibilities. We use Wilson's thinking, as well as Michel Foucault's work on biopower, to forward the concept of biocaring democracy, in which the acceptance of shared pathology compels people to care for each other but also limits their democratic responsibilities. More broadly, our analysis suggests how hinging democracy to shared vulnerability may constrain the radical possibilities that Tronto envisions.